Consumer behavior towards lemongrass (Cybopogon citratus) tea in Benguet Province, Northern Philippines - Dagupen, Marie Klondy T. (Banwa, 2009)
Sensory evaluation was done with 256 respondents who were willing to participate in the study and chosen through sampling based on age and sex. The respondents evaluated pure lemongrass tea and lemongrass with pandan (Pandanus amaryllifolius) using the research questionnaire given to them. Analysis of variance, factor analysis, and cluster analysis were used to assess a degree of association between different study components. Results show that herbal teas were the most favored drinks among the respondents who strongly believe that these help in digestion and relieve stress. The sensory attributes driving acceptability of lemongrass tea were linked to light and clean green colors, citral aroma, and distinct taste. The high acceptability of lemongrass tea mixed with pandan, a locally appreciated herb, shows future possibilities in the product expansion lines.